Leadership and Governance in Islamic Education Institutions: Strategic Planning and the Challenges of Value-Based Education - Sofwan Manaf; Rokimin; Nesa Novrizal; Ahsanul Mufid (CV. Kayaswara, 2026)
This study aims to examine the dynamics of leadership and governance in Islamic education institutions, with a particular focus on how strategic planning is implemented and the challenges encountered in sustaining value-based education. A qualitative research design was employed, utilizing a multiple-case study approach across four Islamic education institutions in Indonesia, including two pesantren and two Islamic universities. Data were collected through semi-structured interviews with 28 institutional leaders, document analysis of strategic plans and governance frameworks, and non-participant observation of institutional practices. Thematic analysis following Braun and Clarke’s six-phase protocol was used to analyze the data. The findings reveal three main themes: (1) the centrality of spiritual leadership in shaping governance structures that align with Islamic values; (2) the tensions between modernization demands and the preservation of traditional educational values; and (3) the role of participatory governance mechanisms in mediating stakeholder interests during strategic planning processes. The study concludes that effective leadership in Islamic education institutions requires an integrative approach that harmonizes Islamic ethical principles with contemporary management practices. This research contributes to the understanding of how value-based governance frameworks can be operationalized within Islamic educational contexts, offering practical implications for institutional leaders and policymakers.